Needs Analysis of Teacher Administration Based on Google Sites in Elementary Schools - Susnita, Deka; Jaenudin, Riswan; Syarifuddin, Syarifuddin (Journal of Educational Sciences, 2023)
This research aims to analyze the administration needs of teachers based on the Google site in elementary schools. At this stage the researcher made observations of several elementary school teachers in Jejawi District regarding the administrative work carried out so far. This interview was conducted during testing with representatives of teacher administration assessors, in order to find out what needs to be improved before the Google Sites-based instrument is used during validation. Data collection in this research used qualitative data. Meanwhile, the data analysis technique also uses qualitative data analysis techniques. Analysis techniques in qualitative research focus more on the details of understanding a problem in depth rather than on the problem as a generalized subject of study. The data that researchers need to analyze is regarding the use of Google Sites as an online service that makes it easier for teachers to more practically download and edit teacher administration data created by researchers in one link. Based on observations of teachers who do administration manually, only 24% of teachers complete administration. It is hoped that this research can increase teacher administration work in elementary schools to 100%. Thus, it can be concluded that this analysis of teacher administration needs is useful for designing and building a Google Sites-based teacher administration system so that teachers can easily organize elementary school teacher administration.